The effect of saffron serum on collagen density, inflammatory gene expression, and autophagy in UVB-exposed Wistar rats - Chitra Octavia; Julia Windi Gunadi; Oeij Anindita Adhika; Lani Ishak; Diana Krisanti Jasaputra; Alexandrina Everdine Rosali; Ardo Sanjaya (Universa Medicina)
Background Skin aging is a complex biological phenomenon influenced by intrinsic and extrinsic factors. Photoaging can be prevented by applying phytochemicals that have sun-protective properties. This study aimed to evaluate the effect of saffron serum to restore collagen density and autophagy processes and reduce inflammatory gene expression in UVB-exposed Wistar rats.